2018
DOI: 10.1186/s40623-018-0789-5
|View full text |Cite
|
Sign up to set email alerts
|

Venus looks different from day to night across wavelengths: morphology from Akatsuki multispectral images

Abstract: Since insertion into orbit on December 7, 2015, the Akatsuki orbiter has returned global images of Venus from its four imaging cameras at eleven discrete wavelengths from ultraviolet (283 and 365 nm) and near infrared (0.9-2.3 µm), to the thermal infrared (8-12 µm) from a near-equatorial orbit. The Venus Express and Pioneer Venus Orbiter missions have also monitored the planet for long periods but from polar or near-polar orbits. The wavelength coverage and views of the planet also differ for all three mission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 95 publications
1
46
0
Order By: Relevance
“…We studied the correlation between the cloud patterns on UltraViolet Imager (UVI) 365‐nm (cloud tops) and IR1 900‐nm (middle clouds) radiance using cylindrical projections of Akatsuki Level‐3 data (Ogohara et al, ). During the MESSENGER's flyby and the Akatsuki mission (Limaye et al, ; Peralta et al, ), NIR and UV images seem uncorrelated in most of the cases. For instance, UV planetary‐scale patterns like the Y feature are absent in NIR images, while the sharp discontinuities in NIR (Figure c) are missing in UV images.…”
Section: Cloud Morphologies At 900 Nmmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied the correlation between the cloud patterns on UltraViolet Imager (UVI) 365‐nm (cloud tops) and IR1 900‐nm (middle clouds) radiance using cylindrical projections of Akatsuki Level‐3 data (Ogohara et al, ). During the MESSENGER's flyby and the Akatsuki mission (Limaye et al, ; Peralta et al, ), NIR and UV images seem uncorrelated in most of the cases. For instance, UV planetary‐scale patterns like the Y feature are absent in NIR images, while the sharp discontinuities in NIR (Figure c) are missing in UV images.…”
Section: Cloud Morphologies At 900 Nmmentioning
confidence: 99%
“…At the upper and middle clouds of Venus, the zonal superrotation exhibits the largest speeds and vertical shear (Sánchez‐Lavega et al, ) and is also where most of the solar energy is deposited (Titov et al, ). The upper clouds' top at ∼70 km (Ignatiev et al, ) can be observed with ultraviolet (UV) and violet wavelengths (∼360–480 nm), with their morphology and dynamics been extensively studied for decades (Belton et al, ; Horinouchi et al, ; Khatuntsev et al, ; Limaye et al, ; Rossow et al, , ; Titov et al, ), thanks to the strong contrasts caused by an unknown absorber (Lee et al, ; Pérez‐Hoyos et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant feature is that there are a large dark area in 283-nm image and a fine cloud complex in 365-nm image. The examples of cloud tracking results are described by Horinouchi et al (2018), and Limaye et al (2018) display the simultaneous images with UVI and other cameras.…”
Section: Operation In the Venus Orbitmentioning
confidence: 99%
“…From its low inclination orbit, Akatsuki provides more low latitude radio occultation profiles (but fewer due to its 10.5-day orbit) compared to the high latitude coverage from Venus Express from its 24 hour polar orbit. Akatsuki results on the Venus cloud cover have been presented by Limaye et al (2018a), the thermal infrared results by and initial thermal structure (35-90 km) results from radio occultations are described by .…”
Section: Introductionmentioning
confidence: 99%